Voltammetry and spectroelectrochemical behavior of a novel octapropylporphyrazinato Lead(II) complex - KOCA, ATIF (AMER CHEMICAL SOC, 2007)
The synthesis, characterization, and voltammetric and spectroelectrochemical investigation of [2,3,7,8,12,13,17,18-octapropyl porphyrazinato] lead(II) are reported. The characterization of newly synthesized lead porphyrazine was made by elemental analysis, H-1 NMR, FT-IR, UV-vis, and MALDI-TOF. The solution redox properties and spectroelectrochemical investigation of the novel lead(II) porphyrazine were studied using various electrochemical techniques in DCM on a platinum electrode. Cyclic voltammetry and differential pulse voltammetry studies show that the complex gives two one-electron ligand-based reductions and a oneelectron oxidation wave having diffusion-controlled mass transfer character. Assignments of the redox couples were confirmed by spectroelectrochemical measurements. Spectroelectrochemical studies reveal that the complex is demetalized during the controlled potential coulometry measurement after the first reduction couple of the complex.
Keywords: OPTICAL LIMITING PROPERTIES; THIN-FILMS; METAL-FREE; PHTHALOCYANINE; ELECTROCHEMISTRY; PORPHYRAZINES; GAS; SUBSTITUENTS; DEMETALATION; SPECTROSCOPY